Investigation of PLC for logic Selectivity Communication in Protection Systems - Salah Boughezala mohammed (International Journal of Energetica)
This paper reports an investigation of power line communication technique PLC for logic selectivity in protection systems. A simulation of power grid with two protection systems using PLC as communication process is performed by Simulink/Matlab program. Also, the attenuation characteristic of high frequency PLC signal is studied regards to resistance, inductance and frequency variation.